The Revitalization of the Great Silk Road: American and Chinese Initiatives - A., Augan M.; A., Bernov V. (Farabi Journal of Social Sciences, 2019)
Abstract.The article is devoted to the implementation of the two New Silk Road initiatives put forward by the USA and The Chinese People’s Republic in order to revitalize ancient trade routes. Authors analyze strategic objectives and different approaches used by the two powers in pursuing their strategies.The attitude of the academic communities towards the projects is also considered. The article conveys aspects of the US-Chinese rivalry.